Heterosis in grain protein content in varietal crosses of rice - Quah, S. C.; Mohan Rao, P. K. (1973)
The extent of heterosis in grain protein content in rice was reported by a few workers: Chao (1972)reported that crosses with early-maturing Japonica varieties showed heterosis in grain protein content and noticed differences between reciprocal crosses.· The present paper deals with heterotic effects in grain protein percentage, grain protein yield and grain protein yield/straw yield ratio in a complete 7-parent diallel cross experiment. Diallel analysis of the data will be published elsewhere.